Performance characteristics of inverter driven synchronous motor - Jenal, Mahyuzie (2009)
Three phase synchronous motor has a wide range of applications. Its constantspeed operation (even under load variation and voltage fluctuation) and high efficiency make it most suitable for constant-speed, continuous-running drives such as motorgenerator sets, air compressors, centrifugal pumps, blowers, crushers and many types of continuous-processing mills. However, this motor is not a self-started type. There are many methods implemented in order to bring up the motor's speed to the required limit. One of the approaches is by using variable-frequency supply starter that is used in this project work. Realizing the importance of motor performance information in practice, this project aimed to carry out the standard motor tests and observe the characteristics. Two main methods are applied in this particular system where one of them is by running up the synchronous motor conventionally. "Prime mover" is coupled to the motor and drives it to the desired speed before supplying electrical sources. The other method is by using variable-frequency (inverter) supply connected to the synchronous motor and run the motor accordingly. A number of experiments are set up either with and without the inverter to analyze and compare their performance characteristics. The results are reported and discussed in this work.